From Disclosure To Trust: Sustaining E-Wallet Usage Through Chatbots - Elfi Elfi (Universitas Merdeka Malang, 2026)
The rapid growth of e-wallet services in Indonesia has increased the use of AI-based chatbots in customer service. While chatbots enhance efficiency, the way they disclose their automated identity may shape users’ psychological and behavioral responses. This study examines the effect of perceived chatbot disclosure quality on trust and continuance intention in Indonesian e-wallet services. Drawing on the Stimulus–Organism–Response framework, disclosure quality is positioned as a communication stimulus, trust as the organismic state, and continuance intention as the behavioral response. A survey of 279 e-wallet users was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived chatbot disclosure quality significantly influences trust and continuance intention. Trust also significantly predicts continuance intention and partially mediates the relationship between disclosure quality and continuance intention. The findings highlight that transparency sustains usage primarily by strengthening trust rather than functioning as a direct behavioral driver.